A systematic review and meta-analysis on the safety of newly adjuvanted vaccines among children. Issue 6 (3rd February 2016) - Stassijns, Jorgen; Bollaerts, Kaatje; Baay, Marc; Verstraeten, Thomas
Highlights: First systematic review of safety of newly adjuvanted vaccines focusing on children. No increased risk of serious and unsolicited adverse events was shown. A higher reactogenicity was observed for all adjuvants. No consistent pattern of solicited adverse events was observed across adjuvants. Abstract: Introduction: New adjuvants such as the AS- or the MF59-adjuvants improve vaccine efficacy and facilitate dose-sparing. Their use in influenza and malaria vaccines has resulted in a large body of evidence on their clinical safety in children. Methods: We carried out a systematic search for safety data from published clinical trials on newly adjuvanted vaccines in children ≤10 years of age. Serious adverse events (SAEs), solicited AEs, unsolicited AEs and AEs of special interest were evaluated for four new adjuvants: the immuno-stimulants containing adjuvant systems AS01 and AS02, and the squalene containing oil-in-water emulsions AS03 and MF59. Relative risks (RR) were calculated, comparing children receiving newly adjuvanted vaccines to children receiving other vaccines with a variety of antigens, both adjuvanted and unadjuvanted. Results: Twenty-nine trials were included in the meta-analysis, encompassing 25, 056 children who received at least one dose of the newly adjuvanted vaccines. SAEs did not occur more frequently in adjuvanted groups (RR 0.85, 95%CI 0.75–0.96). Our meta-analyses showed higher reactogenicity following administration of newly adjuvanted vaccines, however, no consistent pattern of solicited AEs was observed across adjuvant systems. Pain was the most prevalent AE, but often mild and of short duration. No increased risks were found for unsolicited AEs, febrile convulsions, potential immune mediated diseases and new onset of chronic diseases. Conclusions: Our meta-analysis did not show any safety concerns in clinical trials of the newly adjuvanted vaccines in children ≤10 years of age. An unexplained increase of meningitis in one Phase III AS01-adjuvanted malaria trial and the link between narcolepsy and the AS03-adjuvanted pandemic vaccine illustrate that continued safety monitoring is warranted.